In vitro α-glucosidase inhibitory activity of medicinal plants used traditionally for treating diabetes in Vhembe District, South Africa - Stephen O Amoo; Tshenzhemo E Mudau; Joshua O Olowoyo (Shahrekord University of Medical Sciences, 2022)
Introduction: α-Glucosidase is the major enzyme implicated in intestinal glucose absorption, and its inhibition is a target for the management of diabetes mellitus. This study investigated the in vitro α-glucosidase inhibitory activity of extracts from different parts of 20 selected medicinal plants and the potential for plant-part substitution and plant species combinations used by traditional healers to treat diabetes. Methods: Acetone and petroleum ether extracts from different parts of 20 plant species traditionally used to treat diabetes were individually evaluated in vitro using an α-glucosidase assay. The potential for plant-part substitution was investigated by including leaf extracts where non-renewable parts are used traditionally. The extracts of plant species were combined and investigated as used traditionally. Results: Anthocleista grandiflora stem bark acetone, Artabotrys brachypetalus leaf petroleum ether, and Dichrostachys cinerea root petroleum ether extracts exhibited remarkable α-glucosidase inhibitory activities with IC50 values of 9, 14, and 12 μg/mL, respectively. The α-glucosidase inhibitory activities of A. grandiflora, A. brachypetalus, Asparagus virgatus, Brackenridgea zanguebarica, Maerua edulis, Pterocarpus angolensis, and Tabernaemontana elegans were documented for the first time, suggesting their antidiabetic potential. The leaf acetone extracts of Brackenridgea zanguebarica and Terminalia sericea had similar α-glucosidase inhibitory activities when compared to their stem bark and root, respectively. The combination of Dichrostachys cinerea leaf with Elephantorrhiza elephantina root, extracted with petroleum ether, resulted in a synergistic inhibitory effect. Conclusion: The valorization of these newly documented species holds potential for the discovery of more effective and perhaps novel antidiabetic remedies or drug principles.